The influence of TikTok content marketing and price promotion on online purchase intention mediated by online customer trust on The Originote Indonesia at TikTok Shop - Vanessa, Vivian; Heriyadi, Heriyadi; Pebrianti, Wenny; Barkah, Barkah; Fitriana, Ana (Institute of Computer Science (IOCS), 2023)
Social media use penetrated the world of marketing, offering effectiveness and efficiency. TikTok, as one of the social media platforms, had the most users expanding into social commerce as TikTok Shop. The Originote was a well-known newcomer skincare brand in TikTok Shop. The research aimed to test and analyze the impact of TikTok content marketing and price promotion on online purchase intention mediated by online customer trust at The Originote Indonesia. It was a quantitative research in causal associative type. Data was collected using an online questionnaire via Google Forms with a non-probability sampling method, namely the purposive sampling technique. The population was Indonesia TikTok users with the criteria of both females and males over 17 years old, who had watched content on Originote's official account and visited its TikTok Shop. The results showed that content marketing positively and significantly affected online purchase intention and online customer trust. Price promotion positively and significantly affected online purchase intention and online customer trust. Online customer trust as mediation was proven to positively and significantly affect the relationship between content marketing and online purchase intention, as well as the relationship between price promotion and online purchase intention.